Paradoks(i) ničelne tolerance - Sardoč, Mitja (Teorija in praksa, 2015)
This article addresses the zero-tolerance policy approach recently introduced as one of the hallmarks of EU public policy dealing a wide range of social problems. Despite the high profile normally given to different pleas for zero tolerance, there has been no analysis of the moral value and status of the zero-tolerance policy approach. This article aims to advance analysis of the different problems and shortcomings any such policy faces. The introductory part of the paper presents the 'genealogy' of zero tolerance, i.e. the very origin of these policies, and areas that have been the subject of its application in the past few decades. This is followed by a presentation of the 'anatomy' of zero tolerance. The fourth part of the paper outlines the most pressing objections against these policies. The final section identifies the so-called 'paradox' of zero tolerance.
Keywords: Javna politika; Political theories; Political tolerance; Politična tolerantnost; Politične teorije; Public policy; strpnost